(untitled) (Journal of the College of Basic Education, 2023)
The study aimed to know the employment of the potential of digital media in addressing the academic reluctance of students of the Department of Art Education. To achieve the goal of the research, the researcher used the experimental design with two equal groups, with a pre and posttest of academic delay, to suit it on a sample of the third stage students of the Art Education Department. The results of the research The researcher used a number of statistical methods, including;t-test for two independent languages, the equation of difficulty and ease, the equation of discrimination, and the Kewder Richardson equation / 20 The most important results of the search showed; Employing the capabilities of digital media has had an impact in addressing the academic sluggishness of the students of the Department of Art Education . .There is a very high difference between the two responses, before and after, to the academic reluctance of students of the Department of Art Education. Based on the findings of the study, the researcher recommended several recommendations, including: 1- Directing the teaching staff in the Art Education Department of the necessity of increasing interest in providing enrichment and guidance programs for students that contribute to addressing academic reluctance. To complement the current research, the researcher suggested several proposals, including: 1- The effect of the cooperative learning strategy in addressing the academic reluctance of the students of the Department of Art Education in the subject of Art History.